Personality Prediction Based on Sentiment Analysis - Mohd Yazid, Muhamad Haziq Danial (IRC, 2020)
Social media provides an uninterrupted attachment and connectivity, between its user and the external world by revealing personal post/details and their point of view in every aspect of life. The focal aim of this project is to develop a system that can be used to predict personality of social media users and/or author of a text using sentiment analysis. The project main context is to reveal the profiling of these users based on their personality traits by the basis of the dataset. This profiling can become handy and convenient when it comes to career development, job compensation and situation preferences in different surroundings. The personality prediction uses information that is available to the public on the user’s personal social media account using the Big Five Model (Openness, Conscientiousness, Extraversion, Agreeableness & Neuroticism).